The Future of Teaching? Asimov’s Three laws and the Hypothetical Robot Teacher - Robertson, Nicola (PRISM: Casting New Light on Learning, Theory and Practice, 2021)
There is no denying that the influence and use of technology in relation to teaching and learning increased significantly during the Co-Vid-19 periods of isolation and lockdown. The screen became the classroom; the teacher (and the students), rendered as apparitions of virtuality. Nevertheless, despite the barriers of distance and screen, there remained (and indeed remains) something distinctly human about these interactions. What if the teacher on the screen – and, indeed, in the classroom – was not human? Remotely controlled robotic teachers have been trialled in China, with positive feedback from students; yet teaching remains a profession that has been deemed at low risk of automation. This paper will consider Isaac Asimov’s three laws of robotics as a foundational base for predicting the behaviour of a potential, autonomous, robot teacher; comparing the predictions in relation to behaviours deemed as necessary for the successful practice of teaching. To do this, the paper will set out the three hypothetical scenarios, in order to explore – and hopefully determine – whether a ‘robot’ could effectively carry out key teaching activities. The speculative responses to these questions will hopefully inspire further discussion and discourse.